Interface regulation mechanism of Ti doping on B4C/Al composites. Issue 4 (15th February 2023) - Zhang, Liu; Pang, Shaoping; Gu, Wenhao; Luo, Kai; Tian, Rui; Yang, Haowei; Jiang, Yuxing; Yang, Zirun
Abstract: The present work adopts a combination of theoretical calculation and experiment. Firstly, the Gibbs free energy enthalpy change of Ti doped B4 C/Al composites is calculated by thermodynamic principle, revealing the principle that Ti will preferentially combine with Al and B4 C to form TiB2 with excellent performance. Secondly, with the help of spark plasma sintering (SPS) process, pure Al and 4 vol%Ti–Al was used to discuss the degree of interfacial reaction and diffusion between Al–B4 C and Ti/Al–B4 C. It is found that the addition of Ti effectively inhibits the interfacial reaction between Al–B4 C. The kinetic equation of Al diffusion distance and holding time is lnd = 0.66lnt+0.24. Finally, the phase and mechanical properties of two groups of B4 C/Al–Ti and B4 C/Al composites were analyzed. The results showed that the impurity phase of sintering products of Ti doped samples was greatly reduced compared with that of the non doped group, and the mechanical properties were also significantly improved. Ti doping effectively regulates the interfacial reaction of B4 C/Al composites, inhibits the formation of impurity brittle phase in the system, and optimizes the mechanical properties of the composites.